GDY W GRĘ WCHODZĄ POSTAWY: TEATR FORUM W KLASIE JĘZYKOWEJ - Wrońska, Olga (Neofilolog, 2018)
Forum theater is a powerful tool that can enrich teaching with a civic dimension but also improves intercultural intelligence. This paper sets out to bring closer the principles of theater forum and its advantages for teachers and learners. The aim is to present the results of Erasmus+project D.I.A.L.O.G. promoting theater forum at school through workshops and digital multimedia handbook in 4 countries.